Interrelation between fibrosis, angiogenesis and ductular reaction in progression of chronic steatohepatitis (alcoholic and non-alcoholic) and hepatitis C virus infection - O. M. Gavrilyuk (Zaporozhye State Medical University, 2014)
Most specific morphologic signs of chronic hepatitis were studied at early stages of the diseases. Aim. To elucidate the interrelation between fibrosis, angiogenesis and ductular reaction in chronic steatohepatitis and hepatitis C viral infection at the stage of cirrhotic transformation. Methods and results. 45 patients with alcoholic steatohepatitis (ASH), nonalcoholic steatohepatitis (NASH) and hepatitis C viral infection (HCV) at the stage of cirrhotic transformation were enrolled in this study and underwent clinicopathologic examination. The measures of fibrogenesis, angiogenesis and regeneration employed were α-SMA, CD34 and CK19 immunopositive cells respectively. The correlations of these factors with ASH, NASH and HCV were elucidated. Significant ductular reaction was observed only in HCV, whereas low CK19 index could be observed in ASH and NASH. CK19 index in HCV positively correlated with septal fibrosis and angiogenesis. The hepatic neovascularization is proportional to the degree of liver fibrosis in all three diseases. Conclusion. The results indicate that ductular reaction plays an important role in HCV progression at the stage of cirrhotic transformation whereas fibrosis and angiogenesis prevail in ASH and NASH at the stage of cirrhotic transformation.